Early onset cardiovascular disease related to methamphetamine use is most striking in individuals under 30: A retrospective chart review. (June 2022) - Batra, Vinita; Murnane, Kevin S.; Knox, Brianne; Edinoff, Amber N.; Ghaffar, Yahya; Nussdorf, Laura; Petersen, Murray; Kaufman, Sarah E.; Jiwani, Sania; Casey, Christopher A.; Terhoeve, Stephanie; Alfrad Nobel Bhuiyan, Mohammad; et al.
Highlight: Prior MA is associated with an earlier onset of cardiovascular onset which is striking in young adults. Both the races displayed the prior MA use associated earlier age of CVD onset with marked differences in the latency to cardiovascular onset between the Blacks and Whites. Hypertension emerged as the most frequently observed CVD in the MA group. Abstract: Introduction: The illicit use of methamphetamine (MA), a dangerous psychostimulant has become a global epidemic. Studies have demonstrated a link between illicit substance use and cardiovascular consequences. The objective of this study was to assess whether MA use is associated with an early onset of cardiovascular diseases (CVD). Methods: Retrospective analysis was conducted using data collected from 1376 individuals at Louisiana State University Health Sciences Center - Shreveport between 2011 and 2020. Cardiovascular patients with and without a history of MA use were divided into the MA and Control groups. The age of CVD onset was assessed. Descriptive statistics for patient characteristics, Two Samples T-Test for continuous and Pearson's χ^2- tests for categorical variables were calculated. Hazard ratios (HR) and time ratios (TR) were calculated. Results: The age of CVD onset in patients with prior MA use occurred on average 8 year earlier than the age of CVD onset (mean age ± SD = 44 ± 12.04) in controls (mean age ± SD = 52 ± 10.70) (unpaired t -test, p < 0.0001). The findings were noted in both the races (Time Ratio = 0.93, 95% CI = 0.89 to 0.97, p-value < 0.001), with a striking difference in the latency to CVD onset between Black and White subjects. A 12-fold increase in subjects who showed a premature onset of CVD (<30 years of age) in the MA group was observed. Our data analysis revealed that hypertension was the most frequently observed CVD. Conclusions: MA use likely accelerates early onset of CVD and contributes to CVD complications in young adults.